Application of Self-Made Connection Device in Intractable Intramedullary Device. Issue 2 (March 2020) - Lei, Pengfei; Cui, Juncheng; Wang, Wu; Liu, Hao; Luo, Zhenhua; Yang, Xucheng
Abstract : Background: Intramedullary fixation a standard surgical technique for long bone meta/diaphyseal fractures. There were many difficulties in removal of the intractable intramedullary device. The authors reported a new technique to remove the intractable intramedullary nail by using a self-made connecting device. Methods: The subject underwent removal of the intramedullary nail using a self-made connecting device, the core components of which were a caudal connecting rod and a sliding hammer in the common intramedullary nail removal device, and the auxiliary device was mainly a clinically commonly used Kirschner wire (K-wire; diameter 1.5–2.5 mm). In technical procedure, the key point was the connection between the k-wire and the intramedullary device, according to the specific conditions of the intramedullary device. Results: From 2012 to 2017, a total of 10 cases of intractable intramedullary devices were taken out using this self-made connection device, including 7 cases of tibial intramedullary nails, 1 case of femoral nail, and 1 case of tibial elastic nail. The technique provided satisfactory results, no infection or re-fracture occurred after the. Conclusion: The self-made connecting device may provide new technique for more surgeons in the face of intractable intramedullary device. Abstract : Supplemental Digital Content is available in the text